2007
DOI: 10.3168/jds.2007-0200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Prostaglandin and Cytokine Concentrations in Periparturient Holstein Cows Fed Diets Enriched in Saturated or Trans Fatty Acids

Abstract: After parturition, immune functions such as lymphocyte response to mitogens and production of antibodies are depressed in dairy cows. Dietary regimens that improve the immune function of dairy cows after calving may improve uterine health and lead to earlier breeding after parturition. The objective of this study was to examine the effect of feeding a calcium salt of trans isomers of fatty acids (tFA) to periparturient Holstein cows on plasma biomarkers of inflammation. Dietary treatments were initiated approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
5
8
0
2
Order By: Relevance
“…2002). Cows fed LTFA tended to have less complicated cases of metritis (Table 2), which is possibly associated with improved defence against bacterial infection and reduction of pyrexia in those cows, as suggested by others (Rodriguez‐Sallaberry et al. 2007).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…2002). Cows fed LTFA tended to have less complicated cases of metritis (Table 2), which is possibly associated with improved defence against bacterial infection and reduction of pyrexia in those cows, as suggested by others (Rodriguez‐Sallaberry et al. 2007).…”
Section: Discussionsupporting
confidence: 63%
“…2006b). Furthermore, some have suggested that trans ‐octadecenoic fatty acids might influence uterine health and reproductive efficiency of early lactation dairy cows by altering prostaglandin release by the uterus (Rodriguez‐Sallaberry et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasma concentrations of IL‐6 and TNF‐ α in this study were similar to previous measurements in dairy cows (Ishikawa et al., ; Rodriguez‐Sallaberry et al., ; Kasimanickam et al., ; Jahan et al., ; Trevisi et al., ). Nevertheless, the variation of PIC was unexpected at the end of the clamps because generally changes in these mediators are considered to occur quickly after the induction of their release and are short‐lived.…”
Section: Discussionsupporting
confidence: 90%